Management of Educational Facilities and Infrastructure in Madrasahs and Schools - Aburizal; Widya Andriyani; Salis Masruhi; Ahmad Syaifulloh (Al-Qalam Institue, 2025)
This study aims to conceptually examine the management of educational facilities and infrastructure and its role in improving educational quality. The research adopts a qualitative approach using a library research design. Data were collected through a systematic review of relevant literature, including academic books, peer-reviewed journal articles, and educational regulations. The collected data were analyzed using a descriptive-analytical technique with an interpretative approach. The findings indicate that effective and efficient management of educational facilities and infrastructure—encompassing planning, procurement, utilization, maintenance, and disposal—significantly contributes to the creation of a conducive learning environment and the enhancement of instructional quality. Furthermore, school and madrasah leadership plays a strategic role in optimizing the management of educational facilities and infrastructure through professional decision-making and sustainable resource management. This study implies that achieving sustainable educational quality requires synergy between adequate facilities, professional management practices, and effective educational leadership. Strengthening managerial capacity and leadership commitment is therefore essential for improving institutional performance in educational settings.